1931
DOI: 10.1042/bj0252111
|View full text |Cite
|
Sign up to set email alerts
|

The wax constituents of forage grasses

Abstract: IN the present paper an account is given of an investigation into the wax constituents of two very commonly occurring foliage grasses, cocksfoot (Dactylis glomerata) and perennial ryegraos (Lolium perenne). It has not been found possible to obtain as complete an analysis as that recorded in the previous paper dealing with apple-peel wax, but the results are of great interest because they have enabled us to investigate the constitution of a long-chain primary alcohol which is the main constituent of these two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1932
1932
1961
1961

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…The presence of n-nonacosane and 15-nonacosanone in the wax suggested that this secondary alcohol might be 15-nonacosanol, M.P. 83-6-83.80, which had not hitherto been found in natural products, but which had been recently synthesised by Piper et al [1931]. This was confirmed by a mixed melt, which showed no depression.…”
Section: -53°)supporting
confidence: 65%
See 2 more Smart Citations
“…The presence of n-nonacosane and 15-nonacosanone in the wax suggested that this secondary alcohol might be 15-nonacosanol, M.P. 83-6-83.80, which had not hitherto been found in natural products, but which had been recently synthesised by Piper et al [1931]. This was confirmed by a mixed melt, which showed no depression.…”
Section: -53°)supporting
confidence: 65%
“…Each fraction was melted alongside a sample of synthetic 0291160. From the data for mixtures of C29H60 + C31H64 and C27H56 + C2,H given in a previous paper [Piper et al 1931] we conclude that the Brussels sprout paraffin fractions consist of C29H60 with 2*5 to 10 % of C31H64. If the second paraffin had been C30H62 we should not have expected in the case of fraction 4 a fall of nearly 1°in the heating transition-point.…”
Section: -53°)mentioning
confidence: 97%
See 1 more Smart Citation
“…The samples from barley and runner-bean leaves have not hitherto been described. Cocksfoot, one of several samples that collectively had been used to demonstrate that the primary alcohol was Cm, with small amounts of Cm4 and C28 (Pollard et al 1931); wheat, series no. B261 (Pollard, Chibnall & Piper, 1933); apple cuticle, series no C72 (Chibnall et al 1931);lac wax (bulked samples 5, 6, 7, 11, 13 and 14), wild white clover, cactus and white mustard (Chibnall et al 1934); lucerne, series no.…”
Section: Methodsmentioning
confidence: 99%
“…Francis et a2., 6 Pollard et aL5) . [C with a subscript here and in succeeding pages denotes the number of carbon atoms in a long straight-chain compound, e.g. with concentrated hydrochloric acid (10 c.c.).…”
Section: Zsolation Of Waxesmentioning
confidence: 99%